Jesuit teaching in colonial Chile: Its schools, universities, and an approach to its methods and contents - Contreras Gutiérrez, Alejandra (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The document below, aims at reporting on the contribution made by the Company of Jesus to the education in colonial Chile. It provides information about its schools, universities, plans and educational methods. Our idea with this paper, is to establish that with the arrival of the Jesuits to the country and with the starting of the educational work, for the first time the system of education was established in Cali. The methodology used for this work, consists in the revision and collection of data from several texts that are considered classics in the field, as well as, stories of its own order in the country. In such a way as to be able to gather all the information we need to rebuild the overview of the Jesuit education in Chile. As this topic has been so poorly addressed by the national contemporary historiography, our work is intended to make a contribution to the history of education in Chile and Latin America, in the sense that the Jesuit educational experience in Chile, was similar to that experienced in other nations of the continent.